Peningkatan Pemberdayaan Masyarakat Tuban tentang Keamanan dan Kehalalan Pangan dalam Rangka Mempertahankan Kondisi Good Health and Well Being - SDG’s3: Enhancing Empowerment of Tuban Society Regarding Food Safety and Halalness in Order to Maintain Good Health and Well Being -SDG’s3 - Ekowati, Juni; Yuwono, Mochammad; Prayoga, Adistiar; Rosita, Noorma; Purwanto, Bambang Tri; Adrianto, Muhammad Faris; Purwitasari, Neny; Ifadotunnikmah, Farida; Nofianti, Kholis Amalia; Sulistyowaty, Melanny Ika; Suzana, Suzana; Ulvan, Angkasa Megistra; Setiawan, Albertus Aditya; Afandi, Ryan; Wahyuningsih, Etik; Rianti, Dian Ratna; Febrianti, Winanda Rizki (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2024)
The food industry experiences various serious problems when several food MSMEs (micro/small/medium enterprises), especially micro-scale ones, practice improper food manufacturing methods, such as the use of formalin and borax which are prohibited for food preservation, and the marketing of expired food, even repackaged, and the writing of halal labels that are not followed by the fulfillment of requirements. Efforts to prevent things that are detrimental to the community, as well as food and beverage MSME actors, are not only the responsibility of government agencies but also the entire community, including universities for education and assistance in improving the quality and quantity of products produced, as well as the quality of human resources of business actors. The methods used include counseling and skills training, and the outcome is an increase in knowledge of 31%